2014
DOI: 10.1007/s00213-014-3787-8
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent access to nicotine and sucrose in rats

Abstract: Background Animal models that allow concurrent access to drug and nondrug reinforcers provide unique insight into the etiology, maintenance, and treatment of drug use. Objectives We sought to develop and utilize a concurrent access procedure with nicotine and sucrose in rats. Methods Pressing one lever delivered intravenous nicotine, and pressing another lever delivered sucrose pellets, with both reinforcers freely available throughout daily sessions. Results Rats that had been pretrained with nicotine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 55 publications
(65 reference statements)
3
15
0
Order By: Relevance
“…This is consistent with other studies demonstrating that concurrent access to sucrose and nicotine in limited access sessions does not decrease rates of NSA [50,51], unless sucrose availability is contingent upon abstaining from nicotine [50]. Moreover, rats in the present study showed robust NSA despite having ad libitum access to food, which is consistent with other studies showing that food deprivation is not required for nicotine to serve as a reinforce [52,53].…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with other studies demonstrating that concurrent access to sucrose and nicotine in limited access sessions does not decrease rates of NSA [50,51], unless sucrose availability is contingent upon abstaining from nicotine [50]. Moreover, rats in the present study showed robust NSA despite having ad libitum access to food, which is consistent with other studies showing that food deprivation is not required for nicotine to serve as a reinforce [52,53].…”
Section: Discussionsupporting
confidence: 93%
“…In this respect, our results are similar to those of Ferguson and Paule (1995), who found that pre-session vs. post-session feeding had surprisingly little effect on already-established food responding. Pre-session feeding with chow also failed to affect choice between sweet food and nicotine in an earlier study, even though it decreased nicotine self-administration in a drug-only condition (Panlilio et al 2015). The fact that pre-session feeding with chow did not affect choice between food and oxycodone suggests that the motivation driving choice of food in these rats was specific to sweet pellets (Dickinson et al 1996).…”
Section: Discussionmentioning
confidence: 76%
“…Varenicline tartrate (Abcam Pharmaceuticals, Cambridge, UK) was dissolved in 0.9% saline solution which also served as the vehicle control. Doses for Experiments 1 and 2 were selected based on previous studies (Ginsburg and Lamb 2013; LeSage et al 2009; Panlilio et al 2014). Doses for Experiments 4 and 6 were determined based on the outcome of Experiments 1 and 2.…”
Section: Methodsmentioning
confidence: 99%